The Indian Theory of Drama (Global Journal of Human-Social Science, 2021)
Abstract not found
Keywords: kāvya; nātyaśāstra; veda; brahma; bharata; aristotle; asuarās; deva; rūpaka; rasa; bhāvanukirtanm; lokdharmī; natyadharmī